University Students’ Perception of Integrating English Songs into Online English Language Teaching - Rostina Rostina; Dien Afni Ariyati; Sri Hariati Mustari; Ridwan Andi Mattoliang (Jurnal Pendidikan dan Sastra Inggris, 2026)
The use of English songs has been widely discussed as an alternative medium in English language teaching. Songs are believed to create a more enjoyable learning atmosphere and increase students’ motivation, especially in online learning contexts. This study aimed to explore university students’ perceptions of integrating English songs into online English language teaching. This research employed a qualitative descriptive approach. The study was conducted at Universitas Negeri Makassar with first semester students from the Management Study Program who attended an online English language course. The course was delivered fully online using Zoom over one academic semester. English songs were integrated as supporting instructional media during online classes, such as for warm-up activities, listening exposure, and background media. Data were collected through semi-structured written interviews and non-participant observation. The data were analysed using thematic analysis to identify recurring themes related to students’ perceptions. The findings revealed that students generally had positive perceptions toward the use of English songs in online English classes. English songs were perceived to increase students’ motivation and create a more relaxed and enjoyable learning atmosphere. Students also reported higher engagement and attention during online classes when songs were used. In addition, English songs were perceived to support language learning, particularly in improving listening comprehension and vocabulary awareness. However, some challenges were also identified, such as difficulty understanding fast song lyrics, differences in music preferences, and technical issues during online learning. In conclusion, this study suggests that integrating English songs into online English language teaching can provide motivational and pedagogical benefits when used appropriately. English songs can be considered as a supportive instructional medium to enhance students’ engagement and learning experience in online higher education contexts.